Synthesis, characterization, theoretical studies and biological (antioxidant, anticancer, toxicity and neuroprotective) determinations of a copper(II) complex with 5-hydroxytryptophan - Martínez Medina, Juan José (2019)
5-Hydroxy-L-tryptophan (5-HTP) is a serotonin pathway metabolite of L-tryptophan in the brain. In the knowledge that the biological properties of some compounds can be modified upon metal complexation, a new solid metal complex, [Cu(5-hydroxytryptophan) 2 ].H 2 O (Cu5HTP), has been synthesized and characterized to analyze the modification of some biological properties. The conformational investigations (optimized in gas phase at B3LYP/6-311G** theory level) suggest the coexistence of two conformers of Cu5HTP with cis- and trans- arrangements of the amino acids in the equatorial plane. The trans- Cu5HTP1 complex is the most stable conformer. The complexation led to an enhancement of the antioxidant properties of the ligand. The metal complex also improved the anticancer behavior of the ligand (tested in cancer cell lines derived from human lung (A549), cervix (HeLa) and colon (HCT-116)). It did not show toxicity against either the non-malignant human lung fibroblast (MRC-5) cell line or Artemia salina and did not behave as mutagenic agent (Ames test). Cellular reactive oxygen species production may be one of the possible mechanisms of action. Besides, the metal complex exerted neuroprotective action on cortical neurons from embryonic 18 days rats exposed to glutamate.